Evaluation of the effectiveness of photodynamic disinfection on the cytokine profile of oral fluid in patients with chronic generalized periodontitis - L. P. Gerasimova; I. F. Ibragimova; F. Kh. Kamilov; I. A. Lakman; I. N. Usmanova; I. R. Usmanov; T. N. Shaimardanov; A. T. Shaimardanov (Эндодонтия Today)
INTRODUCTION. An emerging and promising direction in dentistry is the use of photodynamically activated disinfection as part of comprehensive therapeutic and preventive protocols. This method contributes to the improvement of clinical periodontal status, enhances immune function, and positively influences the outcomes of periodontal treatment. However, the pathogenetic mechanisms underlying the effectiveness of this therapy remain insufficiently understood and require further investigation. AIM. To evaluate the effectiveness of laser-assisted photodynamic disinfection on the clinical condition of periodontal tissues and the cytokine profile of oral fluid in patients with moderate chronic generalized periodontitis. MATERIALS AND METHODS. A total of 62 patients aged 35 to 45 years with moderate chronic generalized periodontitis were examined. They were randomly assigned to two groups: a control group (receiving standard periodontal treatment) and a main group (receiving photodynamically activated disinfection in combination with standard treatment). Clinical and radiographic examinations were performed, along with the measurement of cytokine levels in oral fluid (IL-1β, IL-4, IL-6, IL-8, IL-10, TNF-α, and IFN-γ) before treatment, and at 14 days, 3 months, and 6 months after treatment initiation. RESULTS. Photodynamically activated disinfection led to a significant improvement in the clinical condition of periodontal tissues and normalization of periodontal and hygiene indices. In addition, patients in the main group demonstrated a restoration of cytokine balance in periodontal tissues, with a marked reduction in proinflammatory cytokines IL-1β, IL-6, IL-8, TNF-α (p < 0.01), and IFN-γ (p < 0.001), as well as an increase in antiinflammatory cytokines IL-4 (p < 0.05) and IL-10 (p < 0.05), compared to baseline levels. CONCLUSIONS. In patients with moderate chronic generalized periodontitis, therapeutic and preventive measures contribute to improved clinical periodontal conditions, as reflected in the periodontal and hygiene indices. However, patients in the main group receiving photodynamically activated disinfection exhibited significantly greater improvements in periodontal indices and normalization of the cytokine profile (p < 0.001).